Corporate social responsibility and cash holdings in Brazilian companies - Moretão, Arthur (2018)
This work examines the effect of corporate social responsibility (CSR) performance on: (i) the value of cash holdings (value model) and (ii) how CSR affects the level of cash holdings in Brazilian companies (cash determinant model). The value model results indicated that investors assign a higher value to excess cash held by high-CSR-performance Brazilian firms, but only when they are subject to a stricter shareholder-protection environment (e.g., cross-listed in the United States). This result is in line with the view that managers should use CSR policies to help mitigate conflicts with stakeholders and the firm in a way that is consistent with shareholders’ interests. The weak institutional environment in Brazil would support the opposite result, albeit the positive relation did not hold true when controlled for corporate governance performance, nor for different specifications of cash holdings. The estimation results for the cash holdings determinants model indicated that CSR performance is positively related to corporate governance, supporting a complementary function of the concepts, as well as the negative relation with idiosyncratic risk indicated reduced risk. The positive relation of CSR performance and systematic risk contrasted with the expected reduced sensitivity to market shocks. CSR performance also had a positive direct effect as well as a negative indirect effect via corporate governance on the level of cash, both statistically significant.